RAMES – Framework supporting user centred evaluation in research and practice. Issue 2 (1st February 2019) - Larusdottir, Marta K.; Gulliksen, Jan; Hallberg, Niklas
ABSTRACT: One way to ensure good user experience of IT systems is to conduct user centred evaluation, aimed to provide feedback to IT professionals on their IT systems from the user perspective. The objective of this paper is to explore a conceptual framework, named RAMES that supports evaluators when planning, comparing and documenting user centred evaluations in a structured way. The framework structures the elements of an evaluation into five categories: Roles, Activities, Materials, Environments, and System. The framework was developed based on a theoretical analysis. Two explorative studies with 92 participants in total show that two thirds of the participants found it easy or rather easy to use the framework, and 33% find it likely that they would use the framework again. The conclusion of the studies is that frameworks such as RAMES enhance the implementation of user centred evaluations.